2014
DOI: 10.1111/mcn.12110
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for raising the maximum acceptable daily intake of EDTA and the benefits for iron fortification of foods for children 6–24 months of age

Abstract: The current maximum acceptable daily intake (ADI) of ethylenediaminetetraacetic acid (EDTA) of 1.9 mg day−1 per kilogram bodyweight (mg day−1 kgbw−1) limits the daily intake of iron as iron EDTA [ferric sodium EDTA; sodium iron(III) EDTA] to approximately 2–2.5 mg day−1 for children 6–24 months of age. This limit was defined by the Joint FAO/WHO Expert Committee on Food Additives (JECFA) in 1973 based on data from an animal-feed study published in 1963. Other animal studies indicate that this limit can be rais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Our conclusion is that humans, after being exposed for a longer time to NTBI values in plasma that can be reached after treatment with highly absorbable iron compounds with a rather moderate increase of serum NTBI, remained healthy. These considerations may contribute to the discussion on the maximum acceptable daily intake of EDTA for iron fortification and iron therapy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our conclusion is that humans, after being exposed for a longer time to NTBI values in plasma that can be reached after treatment with highly absorbable iron compounds with a rather moderate increase of serum NTBI, remained healthy. These considerations may contribute to the discussion on the maximum acceptable daily intake of EDTA for iron fortification and iron therapy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, the iron fortificant used, iron-EDTA, has proven bioavailability in phytate-rich meals like millet, with absorption levels 2 to 3 times higher than with other types of iron, while also increasing the absorption of iron present in other foods included in the diet [ 17 ]. It has been shown to be safe for everyday use, even at a higher dosage and at large scale [ 18 ]. The calcium present in yoghurt could reduce the bioavailability of iron, but the amount provided in one sachet of MNFY was 50 mg, much lower than the level (300 mg) estimated to cause maximal inhibitory effect on iron [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued, however, that this ADI may have been set too low [56], and a recent trial in Moroccan children has shown that daily oral intake of EDTA can reduce blood lead concentrations [57], which is important in view of the enormous public health burden due to lead exposure in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that the fortification dose of 3 mg iron as NaFeEDTA cannot be increased without a substantial proportion of children in this age range exceeding the ADI for EDTA. It has been argued, however, that this ADI may have been set too low [ 56 ], and a recent trial in Moroccan children has shown that daily oral intake of EDTA can reduce blood lead concentrations [ 57 ], which is important in view of the enormous public health burden due to lead exposure in developing countries.…”
Section: Discussionmentioning
confidence: 99%